2020
DOI: 10.1001/jamanetworkopen.2020.0802
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Factors Associated With Opioid Prescriptions for Patients With Pain Conditions in an Urban Emergency Department

Abstract: IMPORTANCEOpioid prescriptions for treatment of pain in emergency departments (EDs) are associated with long-term opioid use. The temporal pattern of opioid prescribing in the context of the opioid epidemic remains unknown. OBJECTIVE To examine the temporal pattern of opioid prescribing within an ED for varying pain conditions between 2009 and 2018. DESIGN, SETTING, AND PARTICIPANTS A population-based, cross-sectional study was conducted at the ED of an urban academic medical center. All patients treated withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…As likely is operative in the study by Smith et al, 1 Downloaded From: https://jamanetwork.com/ on 10/11/2020 for many patients. 5 Not only are these alternatives effective analgesics for most patients, they also avoid the unintended messaging that opioids are the only effective pain management modality.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…As likely is operative in the study by Smith et al, 1 Downloaded From: https://jamanetwork.com/ on 10/11/2020 for many patients. 5 Not only are these alternatives effective analgesics for most patients, they also avoid the unintended messaging that opioids are the only effective pain management modality.…”
mentioning
confidence: 92%
“…Although its latest evolution involves epidemic-level deaths from illicitly manufactured fentanyl and its analogues, the origin of the crisis can be definitively traced to the overprescribing of prescription opioids. Although broad-based efforts across all specialties have resulted in substantial reductions in opioid prescribing, the study by Smith et al 1 demonstrates that efforts in their emergency department (ED) outpaced any secular trend. Their study evaluated opioid prescribing in an urban, academic ED and found a 66.3% decline between 2013 and 2018 for a variety of painful conditions, a rate substantially greater than those reported in previous studies and in national data.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have documented that effective trauma pain management is very important for enhancing patient therapeutic compliance, quality of life, and satisfactory outcomes, which leads to shorter hospital stays [4,5]. Traditional pharmacotherapeutic options for acute pain in trauma settings include different kinds of opioid and non-opioid drugs (e.g., morphine, nitrous oxide, non-steroidal anti-inflammatory drugs) [6][7][8]. However, evidence suggests that these drugs confer an increased likelihood of bleeding, mood disorders, and death in trauma patients [9][10][11].…”
Section: Introductionmentioning
confidence: 99%